Associação entre bem-estar pessoal, sociodemográficos e antropométricos em estudantes universitários - Manoel Borges Silva Junior; Brenda Araújo Lopes; Jordânia Rocha Franco; Douglas Roberto Gomes dos Anjos; Andreza Da Guia Santos Pereira; Elycleia Sousa Silva; José Wicto Pereira-Borges (Universidade de Pernambuco, 2021)
Objective: To analyze the existence of association between personal well-being and sociodemographic and anthropometric variables in university students. Methods: Cross-sectional, analytical study, of a quantitative nature, carried out with university students from a public Higher Education Institution (HEI) based in the city of Floriano-PI. The sample was composed by 279 university students. The data analysis was performed in SPSS version 20.0, to perform analytical statistics. Results: The profile found in most university students was female, young adults, single, who do not have another degree, brown and with family income up to a minimum wage and through some indicators showed low health promotion behavior and dissatisfaction with personal welfare in college students. Conclusion: It was shown that the students are dissatisfied with the association of personal welfare and the sociodemographic and anthropometric data.